Association Between Serum Uric Acid Levels and Traditional Cardiovascular Risk Factors in Xiamen Residents of China: A Real-World Study - Zhang, Peng; Chen, Linjian; Li, Zhaokai; Ni, Wei; Wang, Lin; Mei, Wanchun; Ruan, Guoqiang; Shi, Zaixing; Dai, Cuilian (Frontiers in Cardiovascular Medicine, 2022)
Background: Serum uric acid (SUA) levels was associated with cardiovascular diseases and cardiovascular events. However, the relationship between SUA levels and traditional cardiovascular risk factors has not been well-established among Xiamen residents. Our study aimed to estimate the relationship between SUA levels and cardiovascular risk factors among Xiamen residents using real-world data. Methods: Participants were enrolled from 8 community health service centers in Xiamen, China. Participants were divided into four groups according to quartiles of the SUA levels. The history of diseases, the use of medications and the levels of laboratory parameters were collected. The China-PAR equation was used to evaluate the 10-year atherosclerotic cardiovascular disease (ASCVD) risk. Results: A total of 1322 participants were enrolled. 568 (43.0%) were men and 754 (57.0%) were women. The prevalences of hypertension, elderly, current smokers and obesity were higher in the quartile 4 (Q4) group than the quartile 1 (Q1) group (all p < 0.001). Multivariable logistic regression analysis showed the OR for hypertension was 2.671 (95% CI 1.777 to 4.015, p<0.001) in the Q4 group compared with that in the Q1 group. Further logistic regression showed the OR for hypertension was 3.254 (95% CI 1.756 to 6.031, p<0.001) in men and 2.314 (95% CI 1.354 to 3.955, p = 0.002) in women in the Q4 group compared with that in the Q1 group, respectively. In addition, the percentage of participants with low 10-year ASCVD risk calculated by China-PAR was higher in the Q1 group than that in the Q4 group (55.86% vs. 31.82%, p < 0.001). The percentage of participants with high 10-year ASCVD risk was lower in the Q1 group compared with the Q4 group (15.32% vs. 25.45%, p < 0.001, figure 3). Multiple linear logistic regression showed the 10-year China-PAR ASCVD risk scores was positively correlated with SUA after adjusting for various factors (β = 0.135, p = 0.001). Conclusions: SUA was associated with several cardiovascular risk factors in Xiamen residents. The percentage of high 10-year ASDVD risk was higher in participants with hyperuricemia. Participants with hyperuricemia may experience cardiovascular benefit from uric acid-lowering therapy.